Microbial Community Composition of Two Environmentally Conserved Estuaries in the Midorikawa River and Shirakawa River - Liem, Tran Thanh; Nakano, Mitsuaki; Ohta, Hiroto; Niidome, Takuro; Masuda, Tatsuya; Takikawa, Kiyoshi; Morimura, Shigeru (Graduate School, Universitas Brawijaya, 2016)
To provide a general overview of the microbial communities in environmentally conserved estuaries, the top 5 cm of sediment was sampled from the sandy estuary of the Shirakawa River and from the muddy estuary of the Midorikawa River. Higher amounts of organic matter were detected in the Midorikawa estuary sample than in the Shirakawa estuary sample. Measurement of redox potential revealed that the Shirakawa estuary was aerobic and the Midorikawa estuary was much less aerobic. Clone analysis was performed by targeting partial 16S rRNA gene sequences and using extracted DNA from the samples as a template. Various bacteria were detected, among which Gammaproteobacteria was dominant at both estuaries. Unclassified clones were detected in the Gammaproteobacteria group, mainly among samples from the Midorikawa estuary. Other detected bacterial groups were Alphaproteobacteria, Deltaproteobacteria, Chloroflexi, Actinobacteria, and Bacteroidetes. All the Deltaproteobacteria clones were anaerobic sulfate-reducing bacteria. Those aerobic and anaerobic bacteria coexisted in the top 5 cm of the estuary sediments indicating the surface layer have active sulfur and carbon cycle. Abundance of aerobic Gammaproteobacteria may be an indicator for conserved estuaries. Keywords: conserved environment, clone analysis, estuary, microbial community, 16S rRNA gene.